Pengaruh Pengendalian Internal Terhadap Kinerja Pegawai dengan Self-Esteem sebagai Variabel Moderasi: (Studi Kasus pada Bawaslu Provinsi Jawa Barat dan Bawaslu Kabupaten/Kota Se-Provinsi Jawa Barat) - Herdi Sulaeman (UIN Sunan Gunung Djati Bandung, 2025)
This study aims to examine the interaction between internal control and self-esteem in explaining employee performance. The research was conducted within the organizational environment of the Election Supervisory Board (Bawaslu) of West Java Province, including Bawaslu at the regency and municipal levels. A total of 235 employees were selected as research participants using purposive sampling. This study employs an explanatory research design and utilizes moderated regression analysis to test the moderating effect of self-esteem, with data processing conducted using SPSS software. Data were collected through questionnaires using a Likert scale to measure respondents’ attitudes. The results reveal that self-esteem significantly moderates the relationship between internal control and employee performance. This finding indicates that self-esteem can strengthen the influence of internal control on employee performance.